From tokens to trust: modern approaches to educational data security - Shmatko, O. V.; Kyrychenko, O.; Шматко, О. В. (International Scientific Unity, 2025)
The digitization of education has significantly increased the volume of sensitive student data processed by institutions. This includes not only personal and academic records but also financial and health-related data. Ensuring the confidentiality, integrity, and lawful handling of this data has become a legal and ethical imperative, particularly under regulations such as FERPA (U.S.) and GDPR (EU). This paper explores tokenization and other privacy-enhancing technologies (PETs) as mechanisms for safeguarding student information. We aim to assess their effectiveness, scalability, and integration potential within educational information systems.